2006
DOI: 10.1373/clinchem.2005.062307
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin T Circulates in the Free, Intact Form in Patients with Kidney Failure

Abstract: Background:The clinical significance of the increased concentrations of cardiac troponins observed in patients with end stage renal disease (ESRD) in the absence of an acute coronary syndrome (ACS) is controversial. One proposed explanation is that immunoreactive fragments of cardiac troponin T (cTnT) accumulate in ESRD. We used gel-filtration chromatography (GFC) to ascertain whether fragments of cTnT, which could cross-react in the commercial diagnostic immunoassay (Roche Diagnostics), were the cause of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 26 publications
(31 reference statements)
4
45
0
2
Order By: Relevance
“…Given that cTnI has a lower molecular mass than cTnT (about 22,000 vs. 37,000 Da) [129], the results reported in various studies [9,12,26,47,120,[122][123][124] indicate that there is a larger number of circulating cTnI-related molecules than cTnT-related molecules in healthy subjects. Furthermore, since cTnI and cTnT are present in the sarcomeric complex in a molecular ratio of 1:1, these differences between the circulating cTns are probably related to differences in intra- [130] or extra-cellular [131][132][133] catabolism and the peripheral turnover of cTnI and cTnT.…”
Section: Do Differences In Troponin-dependent 99th Url Values Depend mentioning
confidence: 99%
“…Given that cTnI has a lower molecular mass than cTnT (about 22,000 vs. 37,000 Da) [129], the results reported in various studies [9,12,26,47,120,[122][123][124] indicate that there is a larger number of circulating cTnI-related molecules than cTnT-related molecules in healthy subjects. Furthermore, since cTnI and cTnT are present in the sarcomeric complex in a molecular ratio of 1:1, these differences between the circulating cTns are probably related to differences in intra- [130] or extra-cellular [131][132][133] catabolism and the peripheral turnover of cTnI and cTnT.…”
Section: Do Differences In Troponin-dependent 99th Url Values Depend mentioning
confidence: 99%
“…Some explanations that have been provided include accumulation of immunoreactive fragments of cardiac troponins due to reduced renal clearance (15,16) or continuous cardiac release from limited areas of clinically silent myocardial necrosis (17). Other possible hypotheses are the reexpression of cTnT isoforms in the skeletal muscle fibers during uremic-induced skeletal myopathy (18), the increase of left ventricular mass index (LVMI) (19), the loss of membrane integrity, constant outflow from the free cytosolic troponin pool (20), and uremic damage on myocardial cells (21).…”
Section: Introductionmentioning
confidence: 99%
“…Diris et al (Diris et al, 2004) have shown the presence of immunoreactive cTnT fragments, which are small enough to be cleared by the kidneys and which might accumulate in ESRD patients. Others, however, have found only intact cTnT in patients with kidney failure, (Fahie-Wilson et al, 2006) and to date there is still a great deal of debate on the mechanisms underlying the cTn elevation in ESRD patients. Whatever the exact mechanism, the elevations should not be taken lightly as they are highly predictive for adverse cardiovascular events (Apple, Murakami, Pearce, & Herzog, 2002;Khan, Hemmelgarn, Tonelli, Thompson, & Levin, 2005;Sommerer, Beimler, et al, 2007).…”
Section: Mechanisms Underlying the Ctn Elevationsmentioning
confidence: 99%